Generation Z Within the Workforce and in the Workplace: A Bibliometric Analysis - Benítez-Márquez, María Dolores; Sánchez-Teba, Eva María; Bermúdez-González, Guillermo; Núñez-Rydman, Emma Sofía (Frontiers in Psychology, 2022)
This article aims to improve the knowledge on Generation Z as employees within workforce and in the workplace, as well as on the main thematic trends that drive the research on the topic. To this end, and using bibliometric techniques, a sample of 102 publications on this subject from Web of Science between 2009 and 2020 is analyzed. Research discusses the most published and most cited authors and journals to have a broad view of the context of the subject. Later, through a longitudinal view, the study mainly focuses on analyzing the evolution of thematic clusters, to assess the progress of the themes, as well as the network around the principal motor cluster of each period. The obtained results suggest a hardly developed topic, which started to draw attention in 2018, while still having a wide margin for growth. The core of research on the topic has evolved around “Generation-Z” “generations,” “workplace,” “management” and “attitudes,” “leadership,” “career,” or “learning-teaching-education,” although a low keyword stability among periods was noted. There is a need for further development on a variety of aspects regarding this generation and the labor market, as the study shows a clear orientation toward management and generational diversity within the workplace.